PENERAPAN MODEL PJBL BERBASIS MEDIA WORDWALL DALAM PEMBENTUKAN KARATER KERJASAMA PADA SISWA SEKOLAH DASAR - Fitriana, Erwinda; Wibawa, Sutrisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the effectiveness of the Project-Based Learning (PjBL) model based on Wordwall media in shaping cooperative character among fifth-grade elementary school students with the topic